Social networks, promotions, and the glass-ceiling effect - Michael Neugart; Anna Zaharieva (Journal of Economics & Management Strategy, 2024)
Empirical studies show that women have lower chances of reaching top management positions, known as the glass-ceiling effect. To study women's careers, we develop a search and matching model where job ladders consist of three hierarchical levels and workers can progress in the career by means of internal promotions or by transitioning to another firm. Both, formal applications and referral hiring via endogenous social networks can be used for moving between firms. We show that when female workers are minority in the labor market and social link formation is gender-biased (homophilous), there are too few female contacts in the social networks of their male colleagues. This disadvantage implies that female workers are referred less often and, thereby, become underrepresented in top-level management positions of firms relative to their fraction in the market. Our main theoretical results are consistent with the empirical evidence based on the German Socio-Economic Panel.
Keywords: 330